A rare case of papillary carcinoma in thyroglossal cyst - Dr. Sujata S. Giriyan; Dr. Purushotham Reddy; Dr. Farheen Naaz (Tropical Journal of Pathology and Microbiology, 2018)
Thyroglossal cysts are commonly encountered and may very rarely harbour malignancy. The incidence of carcinoma coexisting in thyroglossal duct cysts is less than 1%, and most common is papillary carcinomas. In the literature to date about 274 cases have been reported. We present a case of a 40 year woman presenting with swelling in front of the neck since 3 months. On examination there was a small firm, non-tender, midline swelling in the neck. Ultrasound examination and contrast enhanced CT showed heterogeneous soft tissue lesion having solid and cystic components with calcification. FNAC showed it to be a benign cystic lesion. After surgical resection, histopathology showed fibro collagenous cyst wall showing thyroid follicular cells with few showing squamous metaplasia and a focal area showing papillae lined by cuboidal cells with nuclear overlapping, grooving and clearing of nuclei suggestive of papillary carcinoma of Thyroglossal Cyst.